Acute Pesticide Poisoning among Mixed-crop Agricultural Workers in Thailand - Somboon, Siriporn; Jirapongsuwan, Ann; Kalampakorn, Surintorn; Tipyamongkolkul, Mathuros (Trends in Sciences, 2022)
Since pesticide exposure has acute health effects on agricultural workers and their communities, the research objectives were to describe the factors contributing to acute pesticide poisoning among mixed-crop agricultural workers in Thailand to guide preventive efforts. A cross-sectional survey using a purposive sampling method was conducted among 102 agricultural workers cultivating rice and ornamental plants in Nakhon Nayok province. Each subject was asked to complete a questionnaire on demographics, symptoms and potential associated factors. The questionnaire had a reliability coefficient range of 0.68 - 0.73. Logistic regression analysis was used to identify the factors associated with the signs and symptoms of acute health effects from pesticide poisoning. The results showed 56.9 % of the participants to be males with an average age of 51.65 years and 88.2 % to have graduated from primary school. Seventy-eight percent of the participants had experienced acute pesticide poisoning within the month preceding data collection. The most common mild signs of the acute health effects of pesticide poisoning were hot, stinging pain on the skin (56.3 %), nasal irritation (56.3 %) and dry throat (38.8 %). The most common moderate symptoms were nausea/vomiting (11.8 %), muscle fatigue/weakness (15.0 %) and chest pain (15.0 %); some workers experienced the severe acute health effect of unconsciousness (1.3 %). The factors contributing to acute pesticide poisoning were age, years of pesticide use and pesticide poisoning prevention behaviors, all of which were significantly correlated with acute pesticide poisoning among the workers (p < 0.05). The findings indicate a need for promoting safe and healthy practice for the mixed-crop agricultural workers in the community. However, recall bias might have occurred from the ability to recall signs and symptoms of agricultural workers. HIGHLIGHTS Most common signs of the acute health effects of pesticide poisoning among mixed- crop agricultural workers were hot, stinging pain on the skin, nasal irritation, dry throat, nausea/ vomiting, and muscle fatigue. Moreover, some workers experienced the severe acute health effect of unconsciousness Factor related to acute pesticide poisoning included age, years of pesticide use, and especially pesticide poisoning prevention behavior